2022
DOI: 10.1007/s13762-021-03905-y
|View full text |Cite
|
Sign up to set email alerts
|

Impact of environmental factors on the spread of dengue fever in Sri Lanka

Abstract: Dengue fever is a mosquito-borne viral disease caused by the dengue virus of the Flaviviridae family and is responsible for colossal health and economic burden worldwide. This study aimed to investigate the effect of environmental, seasonal, and spatial variations on the spread of dengue fever in Sri Lanka. The study used secondary data of monthly dengue infection and the monthly average of environmental parameters of 26 Sri Lankan regions from January 2015 to December 2019. Besides the descriptive measurement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 39 publications
(49 reference statements)
2
23
0
1
Order By: Relevance
“…For example, whilst environmental and sociological considerations often take a back seat in One Health [ 11 ], they frequently occupy the center stage in epidemiology [ 12 ]. Factors such as mean temperatures and rainfall used in predicting dengue [ 1 ], with a very vague consideration of how they affect the mosquito vectors, are an emergent challenge to be considered [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, whilst environmental and sociological considerations often take a back seat in One Health [ 11 ], they frequently occupy the center stage in epidemiology [ 12 ]. Factors such as mean temperatures and rainfall used in predicting dengue [ 1 ], with a very vague consideration of how they affect the mosquito vectors, are an emergent challenge to be considered [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…All studies were conducted monthly, and the results showed that precipitation was substantially associated with dengue incidence. Seven studies indicated that temperature is the second most significant climate variable [ [19] , [20] , [21] , [22] , [23] , [24] , [25] ], followed by relative humidity with four studies [ 19 , 21 , 22 , 26 ] and minimum temperature with three studies [ 23 , 24 , 26 ]. Another study listed significant variables like maximum temperature [ 26 ], atmospheric pressure, sky clearness and wind speed [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
“…Another study listed significant variables like maximum temperature [ 26 ], atmospheric pressure, sky clearness and wind speed [ 20 ]. Most studies were conducted in tropical climates found in Mérida City, México [ 25 ], the Philippines [ 20 , 22 ], and Sri Lanka [ 19 ]. Two studies considered Nakhon Si Thammarat [ 26 ] and Bangkok, Thailand [ 21 ], indicative of the tropical monsoon climate.…”
Section: Resultsmentioning
confidence: 99%
“…Climate plays a vital role in spreading the dengue virus by interfering with the mosquito life cycle (Faruk et al, 2022). This was supported by Wagner et al, (2020), which found that precipitation assists the larvae development stage and hatches mosquito eggs.…”
Section: Literature Reviewmentioning
confidence: 92%